Electrical characteristics of non-thermal dielectric barrier discharge devices with coaxial wire-cylinder and wire-windings configurations - Zulazlan, A.; Lim, M.; Jayapalan, K.K.; Lai, K.L.; Chin, Oi Hoong (Universiti Teknikal Malaysia Melaka, 2016)
o ensure the sustainability of fuel resources and to reduce cost from thermal processes such as combustion, a non-thermal plasma device (NTP) was proposed in this study. NTP devices have been known to reduce pollutants in flue gas and also assist in combustion. As opposed to thermal plasmas, NTPs utilize the energy to create radicals or excited species of the carrier gases that flow through the device. Before the NTP device is applied for combustion, its performance (namely, the amount of energy it consumes and generates) needs to be characterized. Thus, this study investigates the discharge characteristics of two different types of NTP configuration - dielectric barrier discharge (DBD) reactors with (a) wire-cylinder and (b) wire-windings arrangements. The power consumption and discharge power were also measured to determine their efficiency. The discharge power was determined via the Lissajous diagram, which is a plot of the charge accumulated in the discharge against the discharge voltage. The Lissajous diagram of both configurations was a parallelogram, typical of DBDs. The wire-windings arrangement required lower sustaining voltage and was generally more efficient in terms of power consumption.